ANALISIS PIUTANG TERHADAP LIKUIDITAS PERUSAHAAN - Kurniasari, Dian (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2015)
Analysis and Collection of Accounts Receivable Accounts ReceivableTurnover on Corporate Liquidity at CV.JI Semarang, this study aims todetermine the level of turnover and the collection of accounts receivableagainst the debtor that occurred in 2011, 2012 and 2013. Liquidity So thecompany can be found at any period of development.This research used tocollect financial statements consisting of the balance of the year 2011, 2012and 2013. Analytical tool used in this study is the accounts receivableturnover, collecting receivables and liquidity. Data collection techniques usedin the study were interviews with company directors and administrativestaff of one of the debtor company experienced problems in payment.The results of the analysis can be drawn that the company is less efficientin running their business. It can be seen that the development and collectionof accounts receivable turnover tends to decline during the years 2011, 2012,and 2013. This is due to the company's ability to manage its accountsreceivable less well and always has decreased and the increase from year toyear.From the analysis above it can be concluded that the company was notable to maintain stable liquidity (ability) in the company's financialmanagement. So in the last year of the study, in 2013 the companythreatened bankruptcy because of capital related to doubtful accounts is toohigh.